Implantación del sistema de contabilidad comercial en Hormiblock, de la ciudad de Loja, durante el mes de septiembre del 2014 - Jiménez Gordillo, Lady Karina (2015)
The thesis entitled IMPLEMENTATION OF ACCOUNTING SYSTEM IN COMMERCIAL HORMIBLOCK, LOJA CITY DURING THE MONTH OF SEPTEMBER 2014, is a basic accounting tool that will be delivered to the efficient management of the accounting system, and above all serve as information actual economic and financial situation of the company will help its growth, besides allowing to implement all the knowledge acquired during the Race of Accounting and Auditing at the National University of Loja. Its realization allows to comply with the objectives; procedures based on Standards of Generally Accepted Accounting Principles that were useful to achieve mainly the overall objective, starting from the recognition of transactions with source documentation, a chart of accounts was also developed with the corresponding hand, we used the same were the starting point for the development of the accounting process from the initial inventory to obtain the financial statements: Income Statement, Statement of Financial Position and Cash Flow Statement; process safely hereinafter provide real and timely information to HORMIBLOCK. At the end of the present research findings is that among the main accounting system implementation as a tool for controlling operations and a recommendation for their immediate deployment to obtain accurate and timely accounting activities in the company representing information obtained Likewise an alternative solution for the improvement and development of it